PENDIDIKAN ISLAM PADA MASA RASULULLAH SAW - Azzahra, Fatiya Syahidatu; Fahri, Mu’ammar (Proceeding International Seminar of Islamic Studies, 2024)
Islamic education during the time of Prophet Muhammad served as the fundamental basis for shaping a strong and cultured Muslim society. Prophet Muhammad SAW, as the messenger of Allah, played a crucial role in disseminating Islamic teachings and exemplifying Islamic practices. The education during that period encompassed various aspects, ranging from religious teachings and morality to social interaction norms. Prophet Muhammad emphasized religious education, imparting the teachings of the Qur'an and Hadith to his companions. This era was marked by numerous revelations that served as guidance for the lives of the Muslim community. This education was not merely theoretical but practical, with Prophet Muhammad serving as an exemplary figure who embodied Islamic values in everyday life. The teaching methods employed by Prophet Muhammad were highly interactive, involving active participation from his companions. They learned not only from his words but also from his behaviors and attitudes. Islamic education during the time of Prophet Muhammad also included moral aspects, with him educating the community to be individuals characterized by honesty, justice, and high moral standards.